The Use of Antibacterial Drugs and Awareness About the Antibiotic Resistance Problem Among the Students of a Medical University - M. M. Fedotova; V. M. Malchuk; V. A. Churilin; A. A. Zapevalova; D. O. Yakovleva; D. D. Olenius; A. M. Kamenshchikova; S. V. Fedosenko; O. S. Fedorova (Антибиотики и Химиотерапия, 2022)
Background. The growth  of antibiotic resistance is an urgent  problem of modern medicine associated with the irrational use of antibacterial drugs. The solution to this problem requires a comprehensive analysis of the situation not only from the patients’ standpoint, but also from that of medical specialists. Aim. To establish the level of awareness about the problem of antibiotic resistance and to study the practice of antibacterial drug use among senior students of a medical university. Material and methods. A one-time sociological study was conducted in the format of an online survey of the 5th–6th year students of the medical and pediatric faculties of the Siberian State Medical  University of the Ministry of Health  of the Russian Federation. Results. An invitation to the survey was sent to 406 5th–6th year students of the pediatric and medical faculties; 334 students voluntarily completed the questionnaire (return  rate — 82.3%). Most students are aware of the problem of antibiotic resistance. 58.8% of the students took drugs as prescribed by a doctor, adhering to the prescribed duration of treatment. The most  commonly used  antibiotics were: amoxicillin/clavulanic acid — 57.6%, amoxicillin — 29%, azithromycin — 19.4%, ciprofloxacin — 13.4%, 3rd  generation cephalosporins — 8.1%. It was found  that 45.4% of students used  antibiotics parenterally, of which  half (50.4%) performed injections at home or in the dormitory. Up to 89.2% of respondents consider it necessary to use medications to restore the intestinal microflora against the back-ground of antibiotic therapy. Conclusions. Despite the high awareness of the problem of antibiotic resistance and adherence to medical recommendations regarding the use of antibiotics, it is necessary to increase the competence in the field of rational antibiotic therapy for both students and practitioners.